PENGARUH KEPRIBADIAN, SELF-EFFICACY, DAN LOCUS OF CONTROL TERHADAP PERSEPSI KINERJA USAHA SKALA KECIL DAN MENENGAH - Ratno Purnomo; Sri Lestari (Jurnal Bisnis dan Ekonomi, 2010)
Small medium enterprises performance was determined by some factors such asproduction efficiency, marketing strategy, or financial adequacy. But, there is one factor which isimportant for SMEs performance, the enterpreneur itself specially its characteristics. This studyexamined the effects of individual personality, self-efficacy, and locus of control on small mediumenterprises performance in Banyumas. This study used the big five personality approach tomeasure individual characteristics which consists of openness to experience, conscientiousness,extrovertion, agreeableness, and neuroticism (OCEAN). This research used subjective perceptionto measure SMEs performance. This study used survey research design and respondents wereSMEs entrepreneurs located in Banyumas (N = 105). Result of the multiple regression analysisshowed that agreeableness and self-efficacy had a significant and positive effects on SMEsperformance. On the contrary, neuroticism had a significant and negative effect on self-efficacy.Other individual personalities (openness to experience, conscientiousness, and neuritcism) andlocus of control had no significant effect on SMEs performance. Implications for future researchand practice were discussed.Keywords: personality, self-efficacy, locus of control, perfomance, SMEs